RANCANGAN BANGUN E-COMMERCE PENJUALAN PRODUK HERBAL PADA TOKO SHAFA MARWA BERBASIS WEBSITE MENGGUNAKAN PHP NATIVE - Indra Saripulloh, Suhendra Anjar Dinata , Deni Muharam (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2024)
In an era of rapidly developing digital transformation, the industry in Southeast Asia, including Indonesia, is experiencing profound changes with the increasingly widespread adoption of internet technology. In this context, shops as a business sector face pressure to adapt to the needs of consumers who are increasingly connected digitally. One relevant solution is to implement development methods in designing e-commerce based sales applications. The main objective of this researchis to build an effective system for managing and analyzing Shafa Marwa store sales data in order to understand market trends, customer preferences and product availability. In addition, this research aims to create an e-commerce application that offers a personalized shopping experience that suits customer preferences. The research method used is the software development methodused is Rapid Application Development (RAD) and Unified Modeling Language (UML) as a system documentation model. Software testing is carried out through black box testing. Keywords: e-commerce, website, phpnative, online shop, pypment transactions, sales online